Browning's Later Poetry, 1871-1889 - Ryals, Clyde de L. (Cornell University Press, 2019)
Maintaining that Browning's later work has been underestimated, Professor Ryals gives close, sophisticated readings of the individual poems, covering each of the published volumes from Balaustion's Adventure through Asolando. He emphasizes the overall structure of a poem and the manner in which themes and ideas are presented. The later Browning is portrayed as "a poet intent upon discovering forms that would give shape and meaning to thought and experience."
Keywords: Browning, Robert, -- 1812-1889 -- Criticism and interpretation.; Browning, Robert, -- 1812-1889; LITERARY CRITICISM -- Poetry.; Electronic books.; Criticism, interpretation, etc.